The Influence of ChatGPT Usage on the Learning Motivation of Social Studies Education Students at Universitas Negeri Semarang - Prameswari, Venera (Universitas Negeri Semarang, 2025)
The use of artificial intelligence (AI) technology has become increasingly widespread in the field of education to support the learning process, including in enhancing students’ learning motivation. This study aims to analyze the effect of ChatGPT usage on the learning motivation of students in the Social Studies Education Program at Universitas Negeri Semarang. This research employs a quantitative method with a survey design and simple linear regression analysis. The findings reveal that the use of ChatGPT has a positive and significant effect on students’ learning motivation, with a contribution of 56.9%. The analysis is grounded in Self-Determination Theory and Expectancy-Value Theory, which emphasize that ChatGPT contributes to fulfilling basic psychological needs and enhancing expectancy for success and perceived task value. Thus, ChatGPT has proven to be an effective learning support tool that enhances students’ learning motivation. However, its use should be accompanied by sufficient digital literacy and academic guidance to optimize its benefits and minimize the risk of dependency.